2023
DOI: 10.21070/ijins.v21i.752
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Digital Marketing, Brand Equity, and Brand Ambassadors on Interest in Buying Skincare

Abstract: This study aims to determine the effect of Digital Marketing, Brand Equity, and Brand Ambassador on Buying Interest. This study uses a quantitative approach. Sampling in the study used the Probability Sampling technique, with a total of 100 respondents from Lavina Clinic Member Ms Glow. Data collection techniques using questionnaires distributed through questionnaires. The data analysis technique in this study used multiple linear regression analysis. Data processing in this study used the software program SPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
0
0
Order By: Relevance
“…The results of the OLS regression analysis showed that PU, PEOU, SAT, MGC, and UGC all significantly positively impact tourists' intentions to use social media platforms for planning travel to Saudi Arabia. This is in line with earlier findings that demonstrate the impact of these variables on tourists' intentions to use social media platforms for travel planning [35,36,53]. Therefore, Saudi tourism SMEs should consider the relationship between these variables and tourists' intentions to use social media platforms for planning travel to Saudi Arabia in developing their digital marketing strategy on social media.…”
Section: Tourist-based Theoretical Frameworksupporting
confidence: 90%
“…The results of the OLS regression analysis showed that PU, PEOU, SAT, MGC, and UGC all significantly positively impact tourists' intentions to use social media platforms for planning travel to Saudi Arabia. This is in line with earlier findings that demonstrate the impact of these variables on tourists' intentions to use social media platforms for travel planning [35,36,53]. Therefore, Saudi tourism SMEs should consider the relationship between these variables and tourists' intentions to use social media platforms for planning travel to Saudi Arabia in developing their digital marketing strategy on social media.…”
Section: Tourist-based Theoretical Frameworksupporting
confidence: 90%